2012
DOI: 10.1007/s00204-012-0868-5
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors and human disease: an update

Abstract: A myriad of physiological processes in mammals are influenced by estrogens and the estrogen receptors (ERs), ERα and ERβ. As we reviewed previously, given the widespread role for estrogen in normal human physiology, it is not surprising that estrogen is implicated in the development or progression of a number of diseases. In this review, we are giving a 5-year update of the literature regarding the influence of estrogens on a number of human cancers (breast, ovarian, colorectal, prostate, and endometrial), end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
160
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(165 citation statements)
references
References 174 publications
(192 reference statements)
3
160
0
2
Order By: Relevance
“…This mirrors what is seen in high-grade, late-stage prostate cancer (Mak et al 2015). Consequently, it appears that an increase in ERα expression and decrease in ERβ expression is what shifts the balance between protective effects of oestrogens and proliferative effects of oestrogens as has been suggested in other cancers (Barzi et al 2013, Burns & Korach 2012. Figure 3 summarises the difference in ERα and ERβ expression between non-cancerous and cancerous prostate tissue.…”
Section: Oestrogen Receptors (Er) In the Prostatesupporting
confidence: 65%
See 1 more Smart Citation
“…This mirrors what is seen in high-grade, late-stage prostate cancer (Mak et al 2015). Consequently, it appears that an increase in ERα expression and decrease in ERβ expression is what shifts the balance between protective effects of oestrogens and proliferative effects of oestrogens as has been suggested in other cancers (Barzi et al 2013, Burns & Korach 2012. Figure 3 summarises the difference in ERα and ERβ expression between non-cancerous and cancerous prostate tissue.…”
Section: Oestrogen Receptors (Er) In the Prostatesupporting
confidence: 65%
“…This anti-apoptotic effect of ERα makes ERα-positive breast cancers more likely to metastasise (Ross-Innes et al 2012). In fact, a review of ERs in breast and ovarian cancers has found ERα expression correlates with worse prognosis, whereas ERβ expression correlates with better clinical outcomes (Burns & Korach 2012). Generally, ERα activation promotes proliferative pathways, whereas ERβ activation leads to apoptotic pathways (Acconcia et al 2005).…”
Section: Oestrogen Receptors (Er) In the Prostatementioning
confidence: 99%
“…All these molecular mechanisms are operative in breast cancer and affect the pathogenesis and progression of this tumor (recently reviewed by Burns & Korach 2012). It is scarcely conceivable that such molecular mechanisms, at least in part, are not operative in the pathogenesis, recurrence, and metastasis of thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These observations enhance our comprehension of both ER␣ signaling and IQGAP1 function. Importantly, a large body of data implicates both ER␣ (47) and IQGAP1 (27,48) in breast carcinoma. It seems feasible that therapeutic agents directed toward the interaction between ER␣ and IQGAP1 might be useful in the management of patients with breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%